Emerging technologies for developing countries : second EAI International Conference, AFRICATEK 2018, Cotonou, Benin, May 29-30, 2018, Proceedings /: second EAI International Conference, AFRICATEK 2018, Cotonou, Benin, May 29-30, 2018, Proceedings. ([2019]) - Unknown
No abstract available